The uses of fuzzy logic method for finding agriculture and livestock value of potential village - Kurniasih, Dwi; Azmi Jasmi, Kamarul; Basiron, Bushrah; Huda, Miftachul; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
This paper presents the potential owned by the Bulurejo village in the field of Agriculture and Livestock field. The authors conducted a study to determine the outcomes of potential Bulurejo village based on criteria such as potential in the field of agriculture, field of large cattle and small livestock and poultry using fuzzy logic method. So from the results of these studies there are results of the value of 74.29 which is included in the potential of a good village. The application of fuzzy logic method in determining the potential value of the village in accordance with the criteria has been successfully established, so that the fuzzy logic method is suitable for the calculation of the search results from the potential of Bulurejo village.Â Â